2020
DOI: 10.29252/jafm.13.01.29763
|View full text |Cite
|
Sign up to set email alerts
|

Rheological Characterization and Performance Evaluation of Magnetorheological Finishing Fluid

Abstract: The novel controllable behaviour of magnetorheological (MR) fluid is the backbone of magnetorheological fluid-based finishing processes. MR fluid-based finishing processes facilitate better control over finishing forces as the stiffness of MR finishing fluid used in these processes can be controlled in accordance with the applied magnetic field and MR finishing fluid composition. Therefore, a detailed experimental investigation was carried out to find the effect of MR finishing fluid constituents on its yield … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…11b) has been best fitted which is based on the value of the coefficient of regression. The optimized fluid (based on analysis of variance results) exhibits a significant drop in the average surface roughness value [50].…”
Section: Herschel-bulkley Fluid Modelmentioning
confidence: 99%
“…11b) has been best fitted which is based on the value of the coefficient of regression. The optimized fluid (based on analysis of variance results) exhibits a significant drop in the average surface roughness value [50].…”
Section: Herschel-bulkley Fluid Modelmentioning
confidence: 99%
“…V Kumar and other scholars conducted an experimental study on the influence of the composition of magnetorheological polishing fluid on its yield stress through the Taguchi experimental design. The rheological data obtained from the magnetic Rheometer (MCR-102) was characterized by Bingham Plastics, Herschel Bulkley and Casson fluid constitutive models, and used for the finishing of biocompatible stainless steel AISI 316L, with the average surface roughness reduced to 58nm [8]. Scholars such as Jayant studied the magnetorheological abrasive flow finishing process and found that changes in the magnetic field can adjust the viscosity of the magnetorheological fluid and the distribution of abrasive particles.…”
Section: Introductionmentioning
confidence: 99%
“…10 These unique effects have made MRFs of great interest in both academic fields and industrial applications, 11 including dampers, [12][13][14] adsorbents, 15 robotics, 16,17 sensors, 18 and polishing. 19,20 Although many MR devices have successfully entered the prototype stage, commercialization has not yet been achieved due to the lack of effective MRFs with high stability and MR effects.…”
Section: Introductionmentioning
confidence: 99%
“…When the stress caused by the shear load exceeds the yield stress, the highly organized structure deforms, such that the hydrodynamic force becomes dominant over the electrostatic force 10 . These unique effects have made MRFs of great interest in both academic fields and industrial applications, 11 including dampers, 12–14 adsorbents, 15 robotics, 16,17 sensors, 18 and polishing 19,20 . Although many MR devices have successfully entered the prototype stage, commercialization has not yet been achieved due to the lack of effective MRFs with high stability and MR effects.…”
Section: Introductionmentioning
confidence: 99%